Coming through voices of a South Carolina Gullah community from WPA oral histories - Chandler, Genevieve W., 1890-1980; Mills, Kincaid, 1969-; Peterkin, Genevieve C. (Genevieve Chandler), 1928-2011; McCollough, Aaron (University of South Carolina Press, 2008)
Coming Through marks the first complete publication of these interviews with former slaves and their descendants living in the Waccamaw Neck region of South Carolina as collected by Genevieve W. Chandler as part of the WPA Federal Writers Project. Between 1936 and 1938 Chandler interviewed more than one hundred individuals in and around All Saints Parish, a portion of Horry and Georgetown counties located between the Waccamaw River and the Atlantic Ocean. Her subjects spoke freely with her on topics ranging from slave punishment to folk medicine, from conditions in the Jim Crow South to the exploits of Brer Rabbit. --from publisher description.